2007
DOI: 10.1159/000102913
|View full text |Cite
|
Sign up to set email alerts
|

DNA Variation in MSR1, RNASEL and E-Cadherin Genes and Prostate Cancer in Poland

Abstract: Introduction: We investigated whether or not inherited variation in MSR1, RNASEL and E-cadherin contribute to prostate cancer risk in Poland. Material and Methods: We sequenced the coding region of these three genes in individuals from Poland and identified five common DNA variants (R462Q and D541E in RNASEL, R293X and P275A in MSR1, and 2076C>T (A692A) in E-cadherin). These five variants and the –160C>A promoter change in E-cadherin were genotyped in 737 prostate cancer cases and 511 controls. Results: The fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 57 publications
0
13
0
1
Order By: Relevance
“…Two additional studies [29], [30] were added to previous prostate cancer studies [31][38], resulting in a total of 3,570 cases and 3,304 controls. The genotype distribution in controls from two studies [31], [32] was significantly deviated from Hardy-Weinberg equilibrium ( P <0.05).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two additional studies [29], [30] were added to previous prostate cancer studies [31][38], resulting in a total of 3,570 cases and 3,304 controls. The genotype distribution in controls from two studies [31], [32] was significantly deviated from Hardy-Weinberg equilibrium ( P <0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Controls selected in studies investigating the association between the -160C/A polymorphism and prostate cancer risk could be divided into healthy [30], [32], healthy matched [31], [33], [35], [38], benign prostatic hyperplasia [29], healthy and benign prostatic hyperplasia [34], [37] and benign prostatic hyperplasia or others [36]. Subsequent subgroup analysis stratified by controls in data sets of prostate cancer indicated homogeneity in each strata, indicating that the between-study variance in the prostate subgroup resulted from different controls.…”
Section: Resultsmentioning
confidence: 99%
“…In this investigation no association was found between the RNASEL Arg462Gln polymorphism and prostate cancer. Review of some published linkage studies, including a nested case-control study in the USA (3), a population-based study conducted in Sweden (8), a meta-analysis study by Wei et al (17), a German population study (18), a study of prostate cancer in Poland (19) and an analysis of the RNASEL in familial and sporadic prostate cancers by Wang et al (5) did not show any association between the Arg462Gln polymorphism and sporadic prostate cancer risk. In a study by Meyer et al mutation R462Q was only associated with an increased risk in the pre-prostate-specific antigen era and they suggested that this association may be mediated through inflammation (20).…”
Section: Discussionmentioning
confidence: 99%
“…Genotype and allele distributions for each case-control study are shown in Table 2. There were 8 case-controls of the white race (Seppala et al, 2003;Wang et al, 2003;Xu et al, 2003;Maier et al, 2006;Lindmark et al, 2004;Cybulski et al, 2007;Beuten et al, 2010), 1 of the yellow race (Hsing et DOI:http://dx.doi.org/10.7314/APJCP.2015.16.13.5407 The P275A Polymorphism in the Macrophage Scavenger Receptor 1 Gene and Prostate Cancer Risk: a Meta-Analysis al., 2007), 2 of the black race (Miller et al, 2003;Beuten et al, 2010) and 1 of mixed ethnicity (70% Caucasions) (Chen et al, 2008). All the included 10 eligible reports were written in English.…”
Section: Study Inclusion and Characteristicsmentioning
confidence: 99%